Biodegradable materials based on natural silk fabric as promising scaffolds for tissue engineering and regenerative medicine - L. A. Safonova; M. M. Bobrova; A. E. Efimov; O. I. Agapova; I. I. Agapov (Вестник трансплантологии и искусственных органов)
Objective: to develop a method for obtaining scaffolds based on natural silk fabric and to study their biocompatibility in vitro. Materials and methods. To obtain biodegradable scaffolds based on natural silk fabric, we propose treating natural silk fabric with a water-ethanol solution of calcium chloride. Differences in the structure of the resulting scaffolds were identified via scanning electron microscopy. Conclusion. The resulting scaffolds are non-toxic to cells and support cell adhesion and proliferation. Our studies make it possible to consider the resulting biodegradable scaffolds as promising constructs for tissue engineering and regenerative medicine.